Упростите выражения: (3x+y)(2x-5y)-6(x-y)^2=     (-2x^3*y)^3*(-5x^2*y)^2= (-x^2*y^3)^3*(-2x^5*y)^2=

Упростите выражения: (3x+y)(2x-5y)-6(x-y)^2=     (-2x^3*y)^3*(-5x^2*y)^2= (-x^2*y^3)^3*(-2x^5*y)^2=
Гость
Ответ(ы) на вопрос:
Гость
[latex](3x+y)(2x-5y)-6(x-y)^2= \\ = 6x^2-15xy+2xy-5y^2-6x^2+12xy-6y^2=-xy-11y^2[/latex] [latex](-2x^3*y)^3*(-5x^2*y)^2=-8x^9y^3*25x^4y^2=-200x^{13}y^5[/latex] [latex](-x^2*y^3)^3*(-2x^5*y)^2=-x^6y^9*4x^{10}y^2=-4x^{16}y^{11}[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы